Mapping inclusive democracy through communication research: Bibliometric perspectives in Indonesia - Assyari Abdullah; Sumaiyah Sumaiyah; Akmal Khairi; Yasril Yazid; Mustafa Mustafa; Jayus Jayus; Muhammad Soim; Dwi Sutri Astuti; Edison Edison (JURNAL ILMU SOSIAL, 2026)
This study aims to map the development of research on 'inclusive democracy' and 'communication' in Indonesia through a bibliometric approach using data from Dimensions AI. By analyzing 495 publications (402 articles and 93 proceedings) published during the period 2016-2025, this study identifies trends, network collaborations, and thematic clusters that shape the knowledge landscape of inclusive democracy in Indonesia. The analysis was conducted using VOSviewer software to generate network visualizations based on co-authorship, citation, and co-occurrence. The results show that inclusive democracy has experienced significant growth since 2021, especially after the COVID-19 pandemic, which has spurred increased studies on digital participation, transparent governance, and the courage of the public sphere. The main research clusters cover three domains: digital governance, communicative participation, and policy inclusion, confirming the close relationship between communication, technology, and participatory governance. The density of keywords such as democracy, transparency, technology, and community demonstrates that the focus of current research is shifting toward a more inclusive digital democracy based on participatory communication. Thus, this study not only provides an empirical overview of the literature on inclusive democracy in Indonesia but also emphasizes the importance of communication as a key instrument in strengthening democratic legitimacy and representation in the digital era.